2023
DOI: 10.1021/acs.cgd.2c01013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlN and AlGaN Interlayers on AlScN/GaN Heterostructures Grown by Metal–Organic Chemical Vapor Deposition

Abstract: AlScN/GaN heterostructures with their high sheet carrier density (n s ) in the two-dimensional electron gas (2DEG) have a high potential for high-frequency and high-power electronics. The abruptness of the heterointerface plays a key role in the 2DEG confinement, and the presence of interlayers (AlN, AlGaN) affects n s and electron mobility (μ) and determines the sheet resistance (R sh ). AlScN/GaN heterostructures suitable for high-electron mobility transistors (HEMT) with and without a nominal AlN interlayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…[44,48] We demonstrated that a slight modification of the gas mixing system in a commercial MOCVD setup [49,50] could enable the growth of AlScN by MOCVD with standard commercially available cyclopentadienyl-based Sc precursors by heating the source to 150 °C. [45,[51][52][53] We have recently reported that new precursors are under development [54] and feature a higher vapor pressure. However, the only attempt to grow Y-containing nitrides by MOCVD relied on using cyclopentadienyl-based Y precursors (MeCp) 3 Y and (t-BuCp) 3 Y, with the last one enabling doping levels of Y incorporated in GaN (5.3 Â 10 18 cm À3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[44,48] We demonstrated that a slight modification of the gas mixing system in a commercial MOCVD setup [49,50] could enable the growth of AlScN by MOCVD with standard commercially available cyclopentadienyl-based Sc precursors by heating the source to 150 °C. [45,[51][52][53] We have recently reported that new precursors are under development [54] and feature a higher vapor pressure. However, the only attempt to grow Y-containing nitrides by MOCVD relied on using cyclopentadienyl-based Y precursors (MeCp) 3 Y and (t-BuCp) 3 Y, with the last one enabling doping levels of Y incorporated in GaN (5.3 Â 10 18 cm À3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Contactless Hall measurements on AlScN HEMT structures grown on 4 H‐SiC wafers with (MCp)2ScCl (red circles) at different temperatures. The values achieved with Cp3Sc (blue triangles) [ 21 ] are shown for comparison. a) Sheet resistance normalRsh, b) sheet charge carrier density normalnnormals, and c) electron mobility μ are average values obtained for the 100 mm wafers.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical performance of AlScN HEMT structures grown with the novel precursor (MCp)2ScCl (red squares) is compared to the results obtained with Cp3Sc (green triangles), [ 21 ] and our previously published results (black symbols), [ 17,18 ] as well as to the performance of AlScN HEMT structures grown by molecular beam epitaxy (MBE, blue symbols). [ 9,11,28,30 ] Lines of constant sheet resistance are indicated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations